Martensitic Transformation Temperatures of Ceramics. Issue 12 (1st July 2022) - Zarinejad, Mehrdad; White, Tim; Tong, Yunxiang; Rimaz, Sajjad
Abstract : The renewed interest in shape memory and toughened ceramics for small‐scale applications makes the relationship between the chemistry of the ceramics and martensitic transformation temperatures (forward and reverse temperatures M s and A s ) of paramount importance. Dependence of transformation temperatures of the ceramics with shape memory effect and/or martensitic phase change on valence electron ratio (VER), number of valence electrons ( e v ), and average atomic number of the ceramics ( Z ) is investigated. Depending on chemical composition, the ceramics have average numbers of valence electrons (4.571 ≤ e v ≤ 5.667), Z = 13–29.333, and VER in the range of (0.17–0.44). A clear correlation of transformation temperatures to VER for most ceramics is found. M s and A s both decrease with increasing VER. Aliovalent doping alters e v and makes it influential in controlling the transformation temperatures. The influence of VER, e v, Z, and the suppressive effect of oversized solutes on M s is addressed. Abstract : Dependence of transformation temperature of the ceramics with martensitic phase change on valence electron ratio (VER), number of valence electrons ( e v ), and average atomic number of the ceramics ( Z ) is investigated. A clear correlation of transformation temperatures to VER found. The influence of VER, e v, Z, and the effect of oversized solutes on transformation temperatures is addressed.